Effects of Glycerol and Propylene Glycol on Smoke Release of Heat-not-burn Tobacco Products. Issue 2 (March 2021) - Tong, Yuxing; Xiong, Yimin; Yan, Qunshan; Gao, Song; Le, Xi; Wei, Pei; Shu, Hao; Wang, Ziwei; Tang, Xiangbin; Li, Pengfei; Xiong, Zhe; Wang, Yi
Abstract: Glycerin and propylene glycol are the main components of the atomizing agent in heat-not-burn tobacco products (HnB), which affect the smoke release of HnB significantly. In this study, the roles of the glycerin and propylene glycol as the atomizing agent on smoke release of HnB were studied by using a fixed-bed reactor system. The effects of glycerin to propylene glycol ratio in the atomizing agent, and the content of atomizing agent in the HnB were investigated. Gas chromatography-mass spectrometer (GC-MS) was used to analyze the condensable components in the released smoke, and gas chromatography (GC) was used to analyze the gaseous products. The results showed that glycerol could promote the thermal cracking of tobacco and smoke release during pyrolysis. The amount of smoke was the largest when the glycerol ratio was 60%, meanwhile the nicotine content in the smoke was also the highest. When using the glycerin and propylene glycol mixture as the atomizing agent, the amount of smoke and concentration of nicotine and CO in the smoke were increased when the content of atomizing agent decreased in the HnB. The results indicated that the interactions between glycerin and propylene glycol, and the interactions between the atomizing agent and the tobacco were both existed during smoking, which could change the characteristics of the atomizing agent and the smoke release property of HnB.